2022
DOI: 10.21037/atm-22-295
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of extracorporeal shock waves in the treatment of myofascial pain syndrome: a systematic review and meta-analysis of controlled clinical studies

et al.

Abstract: Background: Myofascial pain syndrome (MPS) is recurrent local myofascial pain with various treatment methods. In recent years, extracorporeal shock wave therapy (ESWT) has attracted much attention, but its role still lacks systematic review. We included controlled clinical studies for meta-analysis to systematically evaluate the application effect of ESWT. Methods:The English literature from PubMed, Embase, Cochrane Central Register of Controlled Trials, and Web of Science to October 2021 was searched by compu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 23 publications
(46 reference statements)
2
10
0
1
Order By: Relevance
“…Also, combined with stabilization training, shock wave was found effective in the longterm achieving stable effects for patients with LBP [19]. In addition, ESWT can avoid the adverse effects of invasive procedures on patient tolerance and compliance [20]. However, when comparing our findings with previous studies considering trigger points in other locations than the QL, previous studies showed no significant effects on reducing pain and improving function.…”
Section: Discussionsupporting
confidence: 44%
“…Also, combined with stabilization training, shock wave was found effective in the longterm achieving stable effects for patients with LBP [19]. In addition, ESWT can avoid the adverse effects of invasive procedures on patient tolerance and compliance [20]. However, when comparing our findings with previous studies considering trigger points in other locations than the QL, previous studies showed no significant effects on reducing pain and improving function.…”
Section: Discussionsupporting
confidence: 44%
“…Treatment of MTrPs with ESWT was also applied in a number of other studies that were not considered in the systematic review and meta-analysis performed in [38] [20,22-25,27,28,31,33,37]. However, except for one study [24] ESWT was not compared to injections of lidocaine (or other local anesthetics) in these studies.…”
Section: Discussionmentioning
confidence: 99%
“…During the last decades, extracorporeal shock wave therapy (ESWT) has emerged as an effective and safe alternative for treating MTrPs [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37]. According to a recent systematic review and meta-analysis, ESWT appears to be associated with higher pain alleviation than sham ESWT or ultrasound therapy in treatment of MTrPs in the UTM [38]. Most importantly, there was no statistically significant difference in pain intensity or neck disability index when compared the outcome of ESWT to the outcome of conventional therapies (dry needling, trigger point injection, laser therapy) [38].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Extracorporeal shock waves, acting on human tissues, may produce different physical stress effects in the area of action through the human medium, namely tensile stress and shear force, thereby causing tissue release, improving the microcirculation of muscles and thus relieving the state of muscle spasm in patients ( 68 70 ). A meta-analysis showed that ESWT improves passive joint mobility and muscle properties such as stiffness, tension, and elasticity, which are thought to be related to the rheological properties of shock waves on spastic muscles ( 71 ).…”
Section: Mechanisms Of Eswt In Treating Spasticity After Strokementioning
confidence: 99%